Individuals' Experiences of Having an Unplanned Cesarean Birth: A Qualitative Analysis - DiTosto, Julia D.; Leziak, Karolina; Yee, Lynn M.; Badreldin, Nevert (American Journal of Perinatology, 2022)
Objective The experience of an unplanned cesarean birth may be a risk factor for mood disorders and other challenges in the postpartum period, yet qualitative data on the patient experience are limited. We sought to understand individuals' experiences of having an unplanned cesarean birth.Study Design This was a secondary analysis of a prospective qualitative investigation among low-income postpartum individuals at a single-, tertiary-care center in which the primary aim was to evaluate patients' postpartum pain experience after a cesarean birth. Participants completed a 60-minute face-to-face interview on postpartum days 2 to 3. Only participants who labored prior to their cesarean birth were included in this analysis. Transcripts were analyzed by two separate authors using the constant comparative method. Themes are illustrated using direct quotes.Results A total of 22 individuals were included in this analysis; the majority (n=16, 72.7%) experienced a primary cesarean birth. Over half (n=12, 54.5%) identified as Hispanic and one-third (n=7, 31.8%) identified as non-Hispanic Black race and ethnicity. Four themes regarding the experience of a cesarean birth after labor were identified, including feelings of anguish, belief that vaginal birth is “normal,” poor experiences with care teams, and feelings of self-efficacy. Subthemes were identified and outlined.Conclusion In this cohort, individuals who experienced an unplanned cesarean birth after labor expressed feelings of self-blame, failure, and mistrust. Given the association of unplanned cesarean birth with mood disorders in the postpartum period, efforts to enhance communication and support may offer a means of improving individual experiences.Key Points
Keywords: cesarean birth; qualitative analysis; unplanned cesarean birth